2022
DOI: 10.3390/molecules27238332
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Methodology for Entrapment and Subsequent Removal of Cobalt (II) Ions under Optimized Conditions by Micellar-Enhanced Ultrafiltration

Abstract: Micellar-enhanced ultrafiltration (MEUF), being a separation technique, was used to remove cobalt metal ion (Co2+) from their aqueous solutions in an application to reduce the toxicity level from industrial effluents using a micellar solution of anionic and cationic surfactants. The metal ions were first adsorbed by using anionic surfactants, i.e., sodium dodecyl sulfate (SDS) and sodium oleate (SO). The calculations for partition (Kx) and binding constants (Kb) and their respective free energy of partition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…For example, it was confirmed that high retention of Co(II), Sr(II) and Cs(I) can be obtained (99.6, 99.7 and 97%, respectively) based on filtration with MoS 2 @NH 2 -UiO-66-TFNi membrane [ 49 ]. Furthermore, in the case of Co recovery, micellar-enhanced UF was prosed with the support of two surfactants sodium dodecyl sulfate (SDS) and sodium oleate (SO) with a maximum retention of 99.95 and 99.99%, respectively [ 50 ].…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…For example, it was confirmed that high retention of Co(II), Sr(II) and Cs(I) can be obtained (99.6, 99.7 and 97%, respectively) based on filtration with MoS 2 @NH 2 -UiO-66-TFNi membrane [ 49 ]. Furthermore, in the case of Co recovery, micellar-enhanced UF was prosed with the support of two surfactants sodium dodecyl sulfate (SDS) and sodium oleate (SO) with a maximum retention of 99.95 and 99.99%, respectively [ 50 ].…”
Section: Removal Of Heavy Metalsmentioning
confidence: 99%
“…Surfactants can increase the solubility of drugs because they can create colloidal-sized microemulsions (micelles) in specific liquids [9]. Because surfactants have amphiphilic nature, their molecules self-assemble into micelles at concentrations above the critical micelle concentration (CMC) [10]. Due to their ability to form micelles, amphiphilic surfactants have attracted a lot of attention recently for use in the delivery of drugs.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, MEUF is a very adaptable approach with numerous diverse uses and realworld examples. Current research is dedicated to enhancing the efficiency of surfactant The examined literature [54][55][56] finds many advantages, such as the superior selectivity and efficacy in the elimination of pollutants, flexibility and adaptability in operations, and the fact that it can be integrated with additional treatment techniques, such as activated carbon fibre (ACF), to improve overall effectiveness. Last but not least, the reusability of surfactants is another advantage.…”
mentioning
confidence: 99%